Comparison of the nuclear power industry in Czech Republic and France - Loiseau, Jean-Camille (2010)
This paper studies the nuclear technology and evaluates the most likely technical developments to come until 2030. It examines the features of Czech and French nuclear programs, compares the structures of nuclear sectors and estimates the advantages & drawbacks of further developments in both countries. The paper assesses if certain developments of the nuclear sector in one country can be used in the other country and vice-versa. Finally, proposes a set of recommendations for both countries regarding the development of their nuclear program.